Utilização do método analytic hierarchy process (AHP) para análise das estradas rurais do município de Marechal Cândido Rondon-PR - Heinrich, Cristiano Eduardo (2018)
Brazilian agribusiness is a sector of the economy that has historically demonstrated strength and growth, with emphasis on the agricultural sector that has been presenting production volumes and increasing productivity rates. Despite this, the exceptional competitiveness of Brazilian primary production is gradually diluted as its products leave the rural property to the subsequent links of the productive chains. The logistical obstacles faced by the national agribusiness to transport its wealth are notable, with problems such as the imbalance of the freight transport matrix, depleted transport infrastructure, insufficient static storage capacity and "bottlenecks" in the best known ports. However, little is known about another fundamental component for the logistic efficiency of agribusiness: rural roads. From the moment that the agricultural and livestock production leaves the rural property, the rural road network is the first element with potential of impact to the competitiveness of agribusiness, and few researches were undertaken with this theme. Thus, the present study aimed to investigate and describe the criteria that make a rural road suitable for the transport of inputs and agricultural production. The research was geographically delimited to the municipality of Marechal Cândido Rondon, located in the western mesoregion of the state of Paraná, because this municipality presents its economic base based on agribusiness. The methodology used was the Analytic Hierarchy Process (AHP), since it is able to measure mathematically subjective and objective attributes in a joint way, through comparisons made by individuals with knowledge of the subject matter. The methodological procedures were bibliographic research and non-systematized field survey for initial exploratory analysis, in addition to a survey to deepen the research. A total of 97 interviews were carried out with the application of a form with drivers who transport loads in the rural road network of the municipality. From the initial exploratory survey, 20 criteria potentially relevant to the adequacy of a rural road were related, and the results of the survey indicated a set of 7 priority criteria: integrity and conservation status under satisfactory conditions; track with surface coating that provides better conditions of support and trafficability, mainly asphalt paving; runway with low slope of cross section; full track without deformation; runway without loose / disaggregated materials; platform with adequate surface drainage and low intensity (volume) of traffic. It is concluded, therefore, that these are the attributes of rural roads of greater essentiality for the accomplishment of agribusiness cargo transport activities.